Pemanfaatan Media Sosial Sebagai Sarana Pengembangan Komunitas Virtual - Adelia Ayu Armaya; Aulia Syafitri Yasmin; Della Agustina; Nurbaiti N (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The use of social media as a means of developing virtual communities has significant positive impacts, including increasing cross-cultural understanding, promoting social inclusion, and enabling individuals to build their personal brands or skills. However, challenges related to privacy, security, and sustaining participation also arise. A literature review research method is used to delve into the influence and utilization of social media in virtual communities. The research findings indicate that social media plays a crucial role in facilitating the growth of virtual communities, enhancing participation, and expanding networks. Strategies for utilizing social media such as content marketing, active interaction, and rewards can be employed to maximize its benefits.